2002
DOI: 10.1186/bcr428
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/enhancer binding proteins in normal mammary development and breast cancer

Abstract: 113C/EBP = CCAAT/enhancer binding protein; CHOP = C/EBP homologous protein-10; CUGBP1 = CUG triplet repeat binding protein; IL = interleukin; LAP = liver-enriched activating protein; LIP = liver-enriched inhibitory protein; NF = nuclear factor; PCR = polymerase chain reaction; RT = reverse transcriptase; uORF = upstream open reading frame.Available online http://breast-cancer-research.com/content/4/3/113 IntroductionBreast cancer is, in part, a result of the overexpression of transcription factors that disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 61 publications
(91 reference statements)
1
70
0
1
Order By: Relevance
“…C/EBPβ levels are indeed increased in many tumors (44), and gene expression databases have established that C/EBPβ is an indispensable effector of cyclin D1 transcriptional activity (45). Here, we demonstrated that ALK regulates CEBPB transcription and its protein levels mainly through STAT3.…”
Section: Discussionmentioning
confidence: 63%
“…C/EBPβ levels are indeed increased in many tumors (44), and gene expression databases have established that C/EBPβ is an indispensable effector of cyclin D1 transcriptional activity (45). Here, we demonstrated that ALK regulates CEBPB transcription and its protein levels mainly through STAT3.…”
Section: Discussionmentioning
confidence: 63%
“…PLAC1 Is Selectively Activated by C/EBP␤ Isoform 2-Constitutive expression of C/EBP␤ has been reported in several human tissues, including liver, lung, ovary, placenta, and breast epithelial cells (27)(28)(29)(30). These data required reanalysis as they did not comply with the highly specific expression of C/EBP␤-regulated PLAC1 in the trophoblastic lineage of placental tissue.…”
Section: C/ebp␤ and Sp1 Are Required For Activation Of The Plac1mentioning
confidence: 68%
“…Its aberrant expression has been implicated in the pathogenesis of several epithelial tumors (7)(8)(9) and more recently, in NPM-ALK lymphoid transformation (5,10,11). In ALK þ ALCLs, C/EBPb expression depends on the tyrosine kinase activity of NPM-ALK and is transcriptionnally induced through the STAT3 signaling pathway, although no STAT3-specific binding sites have been observed in the C/EBP promoter region (5,10,11).…”
Section: Discussionmentioning
confidence: 99%